Characterization of Earthworms (Lumbriscus terestris) Population Under Several Area of Shallots Cultivation - M. Anang Firmansyah; Andy Bhermana (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2020)
Firmansyah MA, Bhermana A. 2020. Characterization of earthworms (Lumbriscus terestris) population under several area of shallots cultivation. Jurnal Lahan Suboptimal : Journal of Suboptimal Lands 9(2): 208-217.In General, the problem of shallot commodities development was still used common farming without considering land suitability and other specific soil condition including aspect cultivation. The objective of this study was to clasify several lands characteristics for shallots cultivation and to observe earthworm (Lumbriscus terrestris) population based on their land suitability classes. The methodology used was land evaluation approach and field observation. This study was performed during Â rainy season in 2018 at three locations with different soils, namely, peat soils/Histosol (IST), buried soil of Quartzipsamment above peat soils (ENT), and dry land of Dystropept (EPT). The population of earthworms is obtained by digging up an area of 1 m2 with depth of 20 cm at in four places of location of study. The calculation of earthworms is conducted by hand sorting. The results showed that the highest land suitability class at EPT S3tr, rt, nr, while for other locations are not suitable. The location of IST is classified into N3fb with several limiting such as flooding hazard during rainy season, while for ENT location, classified into Nrt, limiting factor is rough texture. High suitability class is not identical with high earthworm population density. Cultivation aspect that is able to increase soil pH become neutral condition and lower pesticide application affect earthworm populations. ENT locations that have neutral soil pH with lower pesticides applcation have the highest earthworm populations. Earthworm population density from high to low involve ENT> IST> EPT or 74> 33> 31 tails/m2.